Analisis Pemberitaan Positif Terhadap Brand Clothing Lokal: LAKON Indonesia - Amyra Amalia Aqila (Institut Nalanda, 2024)
LAKON Indonesia is one of the local fashion brands that has clothes with unique designs that have an Indonesian touch. LAKON Indonesia has a vision to direct and guide many craftsmen towards a long and sustainable future, and to encourage continuous regeneration so that cultural preservation efforts are maintained. The development of this local brand has made several online news media make LAKON Indonesia as news material that they raise in the mass media. Researchers conducted media monitoring for one month, starting from March 1, 2023 to March 31, 2023 on news about LAKON Indonesia from various media. In carrying out the media monitoring, researchers focused on news that had positive and neutral sentiments towards LAKON Indonesia. The media monitoring was carried out by researchers with the aim of knowing the impact of the positive news on public trust and awareness of the LAKON Indonesia brand.